Ethnobotanical Studies of Koraga Tribal Community of Kasaragod District, Kerala State - N. P. Rajith; N. Mohanan (Journal of Traditional and Folk Practices (JTFP), 2013)
The investigation and analysis of indigenous knowledge of local medicinal curing system may have practical implications for discovering and sustainable development of new medicines. Ethnobotany also encourages an awareness of the link between biodiversity and cultural diversity, as well as a sophisticated understanding of the mutual influence of plants and human beings. The present study highlights the traditional curing art of Koraga tribal community of Kasaragod district for various ailments. The paper reports 42 plant species belonging to 41 genera and 34 families, which are being used in traditional medicine and it gives details of botanical identity, local names, part of the plant used, mode of preparation and dosage.